Integrated analysis of gene expression from carbon metabolism, proteome and metabolome, reveals altered primary metabolism in Eucalyptus grandis bark, in response to seasonal variation. Issue 1 (December 2016) - Budzinski, Ilara; Moon, David; Morosini, Júlia; Lindén, Pernilla; Bragatto, Juliano; Moritz, Thomaz; Labate, Carlos
Abstract Background Seasonal variation is presumed to play an important role in the regulation of tree growth, especially forEucalyptus grandis, a fast-growing tree. This variation may induce changes in the whole tree at transcriptional, protein and metabolite levels. Bark represents an important group of tissues that protect trees from desiccation and pathogen attack, and it has been identified as potential feedstock for lignocellulosic derived biofuels. Despite the growing interest, little is known about the molecular mechanisms that regulates bark metabolism, particularly in tropical countries. Results In this study we report the changes observed in the primary metabolism ofE. grandis bark during two contrasting seasons in Brazil, summer (wet) and winter (dry), through the combination of transcripts (RT-qPCR), proteome (2-DE gels) and metabolome (GC-MS) analysis, in an integrated manner. Twenty-four genes, involved in carbon metabolism, were analyzed in the two seasons. Eleven were up-regulated in summer, three were up-regulated in winter and ten did not show statistical differences in the expression pattern. The proteomic analysis using 2-DE gels showed 77 proteins expressing differences in abundance, with 38 spots up-regulated in summer and 37 in winter. Different metabolites significantly accumulated during winter. Conclusions This study revealed a metabolic reconfiguration in the primary metabolism ofE. grandis bark, triggered by seasonal variation. Transcripts and protein data suggests that during winter carbohydrate formation seems to be favored by tree metabolism. Glucose, fructose and sucrose accumulated at significant levels during the winter.